ANALISIS MODEL DINAMIK PERTUMBUHAN BIOMASSA RUMPUT LAUT GRACILLARIA VERRUCOSA - Kartono., Kartono; Izzati, Munifatul; Sutimin., Sutimin; Insani, Dian (MATEMATIKA, 2008)
The models of growth seaweed Gracillaria biomass are constructed by examining the result observation of patternÂ  growth seaweed Gracillaria biomass in the field. Then, these result are presented by drawing graphic behavior of growth seaweed Gracillaria biomass. This graphic shows that behavior of growth form sigmoidal curve. According to some references the model of growth seaweed Gracillaria biomass is models of logistic growth with constant carrying capacity. The result of analysis show that the amount of biomass to reach maximum when the amount of seaweed Gracillaria biomass same to the carrying capacity.